2001
DOI: 10.1063/1.1370979
|View full text |Cite
|
Sign up to set email alerts
|

Field emission from GaN surfaces roughened by hydrogen plasma treatment

Abstract: GaN layers are grown on sapphire substrates with AlN buffer layers by the metalorganic chemical vapor deposition method. GaN layers are doped with Si. The electron density of the n-type GaN is 2×1017 cm−3. It is found that the GaN surface is etched with hydrogen (H2) plasma produced by supplying microwave power leading to the formation of the roughened surface of GaN. A variation in the surface morphology occurs due to microwave power and gas pressure. Field emission measurements are carried out for GaN with v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
50
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 20 publications
2
50
1
Order By: Relevance
“…Similar results were also observed on NW samples with rough surfaces. 17,[23][24][25] In the growth process of GaN NWs with nanoscale protrusions, it is expected that the Ga vapor reacts with the N vapor, which is decomposed from the NH 3 at a high temperature of 950°C to form the GaN structure. It has been reported that hydrogen has a higher surface mobility and can stream easier and faster than the products of GaN molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were also observed on NW samples with rough surfaces. 17,[23][24][25] In the growth process of GaN NWs with nanoscale protrusions, it is expected that the Ga vapor reacts with the N vapor, which is decomposed from the NH 3 at a high temperature of 950°C to form the GaN structure. It has been reported that hydrogen has a higher surface mobility and can stream easier and faster than the products of GaN molecules.…”
Section: Resultsmentioning
confidence: 99%
“…The previously reported turn-on electric field has ranged approximately between 7 and 133 V/μm for the GaN pyramid arrays and the roughened GaN surface [2][3][4][5], and between 1.25 and 40 V/μm for the GaN nanorod or nanocolumn films [6,7] although it is rather difficult to compare all of them under the same measurement conditions. On the other hand, the values of 1.5 × 10 2 [5] and 4.96 × 10 3 [7] have been reported as β'.…”
Section: Resultsmentioning
confidence: 96%
“…The field conversion factor β, estimated from the slope, ranges from 4.1-5.5 × 10 4 cm -1 using the electron affinity of 2.7-3.3 eV for GaN. Then, the field enhancement factor β' (= βd) is calculated to be 1.2-1.7 × 10 2 , where d is a spacing between the anode electrode and the emitter [5].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, a low threshold voltage was obtained for the tip-like structure, which was formed by growth technique and plasma treatment for BN [8], AlN [9] and GaN [10] systems. Figure 2 shows an atomic force microscopy (AFM) image of the GaN surface grown on Mo substrates at 780 and 700 C. GaN on Mo has a preferential c-orientation and a grain structure.…”
mentioning
confidence: 99%